Compassionate Care: Exploration of the Nurse-Patient Relationship and Behavioral Dynamics in Healthcare Settings - Wagle, Nisha; Neupane, Dasarath; Nyaupane, Netra Prasad; Timalsena, Chiranjibi (International Journal of Atharva, 2024)
The purpose of this study was to assess patients' opinions of nurse behavior and explore the relationship between demographic characteristics and nurse behavior. Four hypotheses have been proposed to investigate the influence of age, gender, marital status, and educational level on nurse behavior. The research methodology was a quantitative, descriptive study using a survey of TU Teaching hospital ward patients. The survey had 45 participants and a 90% acceptance rate. The findings revealed dissatisfaction among patients with the period spent by nurses, while others accepted a lack of affection and belief in the pleasantness of nurses' gestures. However, patients largely believed nurses' clinical evaluations thought their care needs were addressed, and perceived favorable outcomes from nursing treatments. The correlation study indicated no significant relationships between age, gender, marital status, educational level, and nursing behavior. In conclusion, this study provides insight into patient opinions of nurse behavior, highlighting opportunities for improvement.